Efektivitas Ancaman Pidana Mati bagi Pelaku Tindak Pidana Korupsi di Indonesia dari Sudut Padang Hukum, Ham, dan Psikologi - Rosa Pijar Cahya Devi; Yanhizbar Rotanza (Kertha Wicaksana, 2023)
Indonesia occupies the position of a country with a high corruption rate. This is shown by the increase in the corruption perspective index which will increase in 2022 to 43 points. In order to reduce the number of corruptions, policy makers provide a serious threat to corruption cases in Law Number 31 of 1999 on Corruption Crimes. Among the criminal threats imposed, the death penalty is one of the considerations as an appropriate method of punishment for massive corruption cases. The death penalty is expected to reduce the number of corruption crimes in Indonesia. Normative juridical research methods are used in this research to review legislation, research journals, and news relating to corruption and the death penalty. The research results obtained are that the death penalty is not solutive threat to reduce corruption in Indonesia.